Experimental study on the effect of pressure and flow rate on cavitation in a poppet throttle valve. Issue 5 (16th November 2019) - Zhang, Jian; Luo, Tingting
Abstract : Purpose: The purpose of this paper is to study the variation of cavitation scale with pressure and flow in poppet throttle valve, to obtain the cavitation scale under pressure and flow conditions and to provide experimental support for the research of suppressing throttle valve cavitation and cavitation theory. Design/methodology/approach: A hydraulic cavitation platform was set up, a valve was manufactured with highly transparent PMMA material and a high-speed camera was used to observe the change in cavitation scale. Findings: Through experiments, it is found that the pressure difference between inlet and outlet of throttle valve affects the cavitation scale, and the more the pressure difference is, the easier the cavitation will be formed. Under the condition of small pressure difference, the cavitation is not obvious and reducing the pressure difference can effectively suppress the cavitation; the flow rate also affects the cavitation scale, the smaller the flow rate, the more difficult the cavitation will be formed and the lower the flow rate, the more the cavitation will be suppressed. Research limitations/implications: Because of the magnification factor of the high-speed camera lens, the morphology of smaller bubbles cannot be observed in this study, and the experimental conditions need to be improved in the follow-up study. Originality/value: This study can provide experimental support for the study of throttle valve cavitation suppression methods and cavitation theory.